Brief review on medication error prevention and intervention - Vidya, Bhagat; Min Swe, Zaw; San San, Oo (2019)
A failure in the treatment process understood as medication error (ME) leads potential harm to the patient), which is posing a challenge to health care systems across the world. The current short review analyzes on clinical studies on medication errors intervention practices with reduced medication errors. A literature review was completed using electronic databases for this study reviewed 35 articles from the year 2000 to 2018.the articles focused on common medical errors, prevention and interventions. The common errors observed were administration error, dispensing error, prescribing error, preparation error, transcribing error, and reconciliation error. This study concluded knowledge and practice about safe medication administration is evident by decreasing frequency of the errors and interruptions nurses faced during medication administration after intervention. The interventions effective in reducing the occurrence of medication errors evidenced were computerized physician order entry (CPOE), computer-assisted prescription, Clinical Pharmacist intervention. The most common intervention used was CPOE by Clinical Pharmacist and Computerization respectively; which was the most effective intervention strategy, followed by Clinical pharmacist, computerization, Automatic dispensing cabinets, and bar-code. The present study recommends conducting a continuous educational program in the health system is necessary for reducing medication errors and interruptions to protect the patients' safety.